Synthesis of new bile acid-fused tetrazoles using the Schmidt reaction - Škorić, Dušan Đ.; Klisurić, Olivera R.; Jakimov, Dimitar S.; Sakač, Marija N.; Csanádi, János J. (Beilstein Journal of Organic Chemistry, 2021)
A practical and high-yielding Schmidt reaction for the synthesis of fused tetrazoles from bile acid precursors was developed. Mild reaction conditions using TMSN3 instead of hydrazoic acid as an azide source produced good yields of the desired tetrazoles. These conditions could be applied to other steroidal precursors. Additionally, an improved methodology for the synthesis of different ketone and enone precursors from cholic acid, deoxycholic acid, and chenodeoxycholic acid was established. Newly obtained tetrazole derivatives were characterized by NMR and X-ray diffraction spectroscopy. In a number of cases, preliminary antiproliferative tests of new compounds showed strong and selective activity towards certain tumor cell lines.
Keywords: antiproliferative activity; Schmidt reaction; steroids; tetrazoles; trimethylsilyl azide

(untitled) - Stofan, M.; Guo, G. L. (Front. Med., 2020)

(untitled) - Sepe, V.; Distrutti, E.; Limongelli, V.; Fiorucci, S.; Zampella, A. (Future Med. Chem., 2015)

(untitled) - Pols, T. W. H.; Noriega, L. G.; Nomura, M.; Auwerx, J.; Schoonjans, K. (Dig. Dis., 2011)

(untitled) - Pellicciari, R.; Passeri, D.; De Franco, F.; Mostarda, S.; Filipponi, P.; Colliva, C.; Gadaleta, R. M.; Franco, P.; Carotti, A.; Macchiarulo, A.; Roda, A.; Moschetta, A.; et al. (J. Med. Chem., 2016)

(untitled) - Festa, C.; Renga, B.; D’Amore, C.; Sepe, V.; Finamore, C.; De Marino, S.; Carino, A.; Cipriani, S.; Monti, M. C.; Zampella, A.; Fiorucci, S. (J. Med. Chem., 2014)

(untitled) - Macchiarulo, A.; Gioiello, A.; Thomas, C.; Pols, T. W. H.; Nuti, R.; Ferrari, C.; Giacchè, N.; De Franco, F.; Pruzanski, M.; Auwerx, J.; Schoonjans, K.; Pellicciari, R. (ACS Med. Chem. Lett., 2013)

(untitled) - Gioiello, A.; Venturoni, F.; Tamimi, S.; Custodi, C.; Pellicciari, R.; Macchiarulo, A. (Med. Chem. Commun., 2014)

(untitled) - Faustino, C.; Serafim, C.; Rijo, P.; Pinto Reis, C. (Expert Opin. Drug Delivery, 2016)

(untitled) - Darkoh, C.; Lichtenberger, L. M.; Ajami, N.; Dial, E. J.; Jiang, Z.-D.; DuPont, H. L. (Antimicrob. Agents Chemother., 2010)

(untitled) - Poša, M.; Csanádi, J.; Kövér, K. E.; Guzsvány, V.; Batta, G. (Colloids Surf., B, 2012)

(untitled) - Aleksić Sabo, V.; Škorić, D.; Jovanović-Šanta, S.; Nikolić, I.; János, C.; Knežević, P. (J. Ethnopharmacol., 2021)

(untitled) - Bjedov, S.; Jakimov, D.; Pilipović, A.; Poša, M.; Sakač, M. (Steroids, 2017)

(untitled) - Bjedov, S.; Jakimov, D.; Poša, M.; Klisurić, O. R.; Sakač, M. (Tetrahedron, 2017)

(untitled) - Poša, M.; Bjedov, S.; Škorić, D.; Sakač, M. (Biochim. Biophys. Acta, Gen. Subj., 2015)

(untitled) - Ostrovskii, V. A.; Trifonov, R. E.; Popova, E. A. (Russ. Chem. Bull., 2012)

(untitled) - Herr, R. J. (Bioorg. Med. Chem., 2002)

(untitled) - Bansal, R.; Acharya, P. C. (Chem. Rev., 2014)

(untitled) - Jourdan, F.; Bubert, C.; Leese, M. P.; Smith, A.; Ferrandis, E.; Regis-Lydi, S.; Newman, S. P.; Purohit, A.; Reed, M. J.; Potter, B. V. L. (Org. Biomol. Chem., 2008)

(untitled) - Zhang, J.; Wang, S.; Ba, Y.; Xu, Z. (Eur. J. Med. Chem., 2019)

(untitled) - Demko, Z. P.; Sharpless, K. B. (Angew. Chem., Int. Ed., 2002)

(untitled) - Schmidt, K. F. (Ber. Dtsch. Chem. Ges. B, 1924)

(untitled) - Amyes, T. L.; Richard, J. P. (J. Am. Chem. Soc., 1991)

(untitled) - Gu, P.; Kang, X.-Y.; Sun, J.; Wang, B.-J.; Yi, M.; Li, X.-Q.; Xue, P.; Li, R. (Org. Lett., 2012)

(untitled) - Li, X.-J.; Qiao, J.-B.; Sun, J.; Li, X.-Q.; Gu, P. (Org. Lett., 2014)

(untitled) - Cervantes, A.; Crabbe, P.; Iriarte, J.; Rosenkranz, G. (J. Org. Chem., 1968)

(untitled) - Hajra, S.; Bhowmick, M.; Sinha, D. (J. Org. Chem., 2006)

(untitled) - Omura, M.; Iwanami, K.; Oriyama, T. (Chem. Lett., 2007)

(untitled) - Motiwala, H. F.; Charaschanya, M.; Day, V. W.; Aubé, J. (J. Org. Chem., 2016)

(untitled) - Li, L.-H.; Niu, Z.-J.; Li, Y.-X.; Liang, Y.-M. (Chem. Commun., 2018)

(untitled) - Stoltz, K. L.; Erickson, R.; Staley, C.; Weingarden, A. R.; Romens, E.; Steer, C. J.; Khoruts, A.; Sadowsky, M. J.; Dosa, P. I. (J. Med. Chem., 2017)

(untitled) - Bukiya, A. N.; Patil, S. A.; Li, W.; Miller, D. D.; Dopico, A. M. (ChemMedChem, 2012)

(untitled) - Kádár, Z.; Kovács, D.; Frank, É.; Schneider, G.; Huber, J.; Zupkó, I.; Bartók, T.; Wölfling, J. (Molecules, 2011)

(untitled) - Uzzaman, S.; Asif, M.; Ali, A.; Mashrai, A.; Khanam, H.; Sherwani, A.; Owais, M. (Eur. Chem. Bull., 2014)

(untitled) - Gogoi, J.; Bezbaruah, P.; Saikia, P.; Goswami, J.; Gogoi, P.; Boruah, R. C. (Tetrahedron Lett., 2012)

(untitled) - Penov-Gaši, K. M.; Oklješa, A. M.; Petri, E. T.; Ćelić, A. S.; Djurendić, E. A.; Klisurić, O. R.; Csanadi, J. J.; Batta, G.; Nikolić, A. R.; Jakimov, D. S.; Sakač, M. N. (Med. Chem. Commun., 2013)

(untitled) - Moural, J.; Syhora, K. (Collect. Czech. Chem. Commun., 1970)

(untitled) - Ahmad, M. S.; Chaudhry, Z. H.; Khan, P. N. (Aust. J. Chem., 1976)

(untitled) - Dwivedy, I.; Singh, A. K.; Singh, M. M.; Ray, S. (Steroids, 1993)

(untitled) - Alam, M.; Nami, S. A. A.; Husain, A.; Lee, D.-U.; Park, S. (C. R. Chim., 2013)

(untitled) - Rasras, A. J. M.; Al-Tel, T. H.; Al-Aboudi, A. F.; Al-Qawasmeh, R. A. (Eur. J. Med. Chem., 2010)

(untitled) - Iuliano, A.; Facchetti, S.; Uccello-Barretta, G. (J. Org. Chem., 2006)

(untitled) - Kuhajda, K.; Kandrač, J.; Cirin-Novta, V.; Miljković, D. (Collect. Czech. Chem. Commun., 1996)

(untitled) - Fieser, L. F.; Rajagopalan, S. (J. Am. Chem. Soc., 1950)

(untitled) - Fieser, L. F.; Rajagopalan, S.; Wilson, E.; Tishler, M. (J. Am. Chem. Soc., 1951)

(untitled) - Myers, E. L.; Butts, C. P.; Aggarwal, V. K. (Chem. Commun., 2006)

(untitled) - Litkei, G.; Patonay, T. (Acta Chim. Hung., 1983)

(untitled) - Mphahlele, M. J. (Trends Org. Chem., 2009)

(untitled) - Reddy, D. S.; Judd, W. R.; Aubé, J. (Org. Lett., 2003)

(untitled) - Bach, R. D.; Wolber, G. J. (J. Org. Chem., 1982)

(untitled) - Macrae, C. F.; Sovago, I.; Cottrell, S. J.; Galek, P. T. A.; McCabe, P.; Pidcock, E.; Platings, M.; Shields, G. P.; Stevens, J. S.; Towler, M.; Wood, P. A. (J. Appl. Crystallogr., 2020)

(untitled) - Mosmann, T. (J. Immunol. Methods, 1983)

(untitled) - Jakimov, D. S.; Kojić, V. V.; Aleksić, L. D.; Bogdanović, G. M.; Ajduković, J. J.; Djurendić, E. A.; Penov Gaši, K. M.; Sakač, M. N.; Jovanović-Šanta, S. S. (Bioorg. Med. Chem., 2015)